BUILDING WEBSITE TALIMERAH.COM WITH MACROMEDIA FLASH 5.0 - Hendra Azis; Hariyanto Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 2004)
The development program for web applications is one thing that becomes the motivation and challenge to the designer and creator of the website is to further improve the quality of websites that they make, in order to compete with pernacang makers and other websites. The development of technology for web designing and manufacturing animatif already begun at the time of the Macromedia Flash attendance, Karen aflash is an application program that can create animation which is very dynamic and can be used for making a website in order to become animatif. Presents an interesting website, and not saturated in terms of appearance is a fundamental problem for designing websites. Layout, game color and animation are elements that need to be taken into account in making a website, then the application of science in graphic design and application programs such as Macromedia Flash to be the main thing in designing websites. Realizing that the future world of information is the internet, then the scientific writing of the author tries to build a website with the view that animatif using Macromedia Flash 5.0 on the website or homepage talimerah.com